MEASURING THE ZAKAT VILLAGE INDEX IN SUPPORTING THE ZAKAT COMMUNITY DEVELOPMENT PROGRAM AT BAZNAS GORONTALO DISTRICT - Muhibbuddin, Muhibbuddin; Sahabi, Ansar; Raupu, Mutiara; Abdullah, Faisal; Rahman, Supandi (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2024)
Abstract Calculation of the Village Zakat Index Value is the aim of research conducted in Buhu, Iloponu, East Limehe, Toyidito and Tonala Villages. The method used is a descriptive quantitative approach. The samples in this study were the 5 poorest villages in Gorontalo Regency, namely Buhu Village, Iloponu Village, East Limehe Village, Toyidito Village, and Tonala Village. Data collection instruments through observation, questionnaires and documentation. By using primary data sources obtained directly from respondents related to research and secondary data obtained from books, journals and previous research. The informants in this research were village officials and the community. The results of the Zakat Index calculation, Tonala Village has the lowest overall index value of 0.45. Thus, this figure is in the quite good category, so consideration needs to be taken when providing assistance. Keywords: Zakat Village Index, Zakat Community Development Abstrak Perhitungan Nilai Indeks Desa Zakat merupakan tujuan dari pada penelitian yang dilakukan di Desa Buhu, Iloponu, Limehe Timur, Toyidito dan Desa Tonala. Metode yang digunakan yakni pendekatan kuantitatif Deskriptif. Sampel pada penelitian ini adalah 5 Desa termiskin di Kabupaten Gorontalo yaitu Desa Buhu, Desa Iloponu, Desa Limehe Timur, Desa Toyidito, dan Desa Tonala. Instrumen pengumpulan data melalui observasi, angket dan Dokumentasi. Dengan menggunakan sumber data primer diperoleh langsung dari responden yang berkaitan dengan penelitian dan data sekunder diperoleh dari buku, jurnal dan penelitian terdahulu. Informan dalam penelitian ini adalah aparat desa dan masyarakat. Hasil perhitungan Indeks Zakat, Desa Tonala memiliki nilai indeks terendah secara keseluruhan sebesar 0,45. Dengan demikian, angka ini berada pada kategori cukup baik, sehingga perlu adanya pertimbangan dalam pemberian bantuan. Kata Kunci: Indeks Desa Zakat, Zakat Community Development